Homeostasis of Hemostasis: The Role of Endothelium - Kazmi, Rashid S.; Boyce, Sara; Lwaleed, Bashir A. (Seminars in Thrombosis and Hemostasis, 2015)
Forming an interface with virtually every other organ, endothelium has a strategic role in modulating vascular homeostasis. While its miscellany of functions includes regulation of vasomotor tone, promotion, and prevention of vascular growth, and modulation of inflammatory and hemostatic processes, it functions critically in maintaining the balance of hemostasis in health. Whereas endothelium has been recognized to influence all stages of hemostasis, new evidence suggests it to have a primary role for thrombin generation. Endothelial dysfunction is being increasingly appreciated in several pathological states and particularly, by virtue of its critical role in hemostasis, in causing thrombosis in a multitude of diseases.
Keywords: endothelium; endothelial dysfunction; homeostasis; hemostasis; thrombosis